FiqhTasawuf in the Book of Asrarus Shalat by Tuan Guru Abdurrahman Shiddiq Al-Banjari: Analysis of Sharia and the Essence of Prayer - Amaruddin, Amaruddin; Umar, M. Hasbi; Una, Sayuti (International Journal of Multidisciplinary Approach Research and Science, 2025)
The relationship between fiqh and tasawuf is a problem that often arises, especially in the practice of prayer. Tuan Guru Abdurrahman Shiddiq Al-Banjari has formulated an analysis of the correlation between fiqh and tasawuf, or in other words, sharia and essence in the practice of prayer, as stated in his book Asrarus Shalat Min ’Iddati Kutubil Mu’tamadat (often referred to as Asrarus Shalat), a book that contains the secrets of prayer. This study aims to determine and analyze the problem of the correlation between fiqh/sharia and tasawuf/essence in prayer, especially in the discussion in the book Asrarus Shalat Min ’Iddati Kutubil Mu’tamadat by Tuan Guru Abdurrahman Shiddiq Al-Banjari. Methodologically, the study uses a qualitative method, by applying a library research approach, namely conducting a study of a problem and orienting it towards library data sources or related literature. The results or findings of this study are the relevance between fiqh/sharia and tasawuf/essence in prayer. The connection between fiqh and tasawuf is a requirement for achieving the perfection of prayer, both outwardly and inwardly. In addition, the book Asrarus Shalat contains three discussions, namely the principles of prayer, the virtues of prayer, and the meaning of prayer readings. Analysis of the relevance between sharia and essence can be seen in the principles of prayer, by dividing it into two parts, namely the principles of the outer world oriented towards fiqh/sharia, such as, conditions, pillars, cancellations, and sunnah of prayer; and the inner world oriented towards tasawuf/essence, such as knowing the secrets of the conditions and pillars of prayer, and believing the essence of the secrets of prayer with all one’s heart. The research serves as a recommendation and reference for teachers, students, and the Indragiri Hilir community, in recognizing, preserving, understanding, and applying all the teachings of Tuan Guru Abdurrahman Shiddiq Al-Banjari, especially those contained in his works, such as the book Asrarus Shalat Min ’Iddati Kutubil Mu’tamadat.